2021
DOI: 10.1101/2021.03.24.436805
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular Matrix Hydrogels Promote Expression of Muscle-Tendon Junction Proteins

Abstract: Muscle and tendon injuries are prevalent and range from minor sprains and strains to traumatic, debilitating injuries. However, the interactions between these tissues during injury and recovery remain unclear. Three-dimensional tissue models that incorporate both tissues and a physiologically relevant junction between muscle and tendon may aide in understanding how the two tissues interact. Here, we use tissue specific extracellular matrix (ECM) derived from muscle and tendon to determine how cells of each tis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Together with our results demonstrating that COL22A1 interface between muscle and tendon reversibly elongates under tensile loading, these data indicate that COL22A1 connects the ECM between muscle and tendon. While multiple cell types have been hypothesized to synthesize COL22A1 at the MTJ, including muscle (Kim et al, 2020;Koch et al, 2004;Subramanian and Schilling, 2015), tendon/connective tissue (Scott et al, 2019;Yaseen et al, 2021), or both (Gaffney et al, 2021;Petrany et al, 2020), our data revealed that COL22A1 integration requires the presence of muscle in the limb.…”
Section: Tendon and Epimysial-like Ecm Formed In The Absence Of Musclementioning
confidence: 49%
“…Together with our results demonstrating that COL22A1 interface between muscle and tendon reversibly elongates under tensile loading, these data indicate that COL22A1 connects the ECM between muscle and tendon. While multiple cell types have been hypothesized to synthesize COL22A1 at the MTJ, including muscle (Kim et al, 2020;Koch et al, 2004;Subramanian and Schilling, 2015), tendon/connective tissue (Scott et al, 2019;Yaseen et al, 2021), or both (Gaffney et al, 2021;Petrany et al, 2020), our data revealed that COL22A1 integration requires the presence of muscle in the limb.…”
Section: Tendon and Epimysial-like Ecm Formed In The Absence Of Musclementioning
confidence: 49%